Data from: Spatial scale and specialization affect how biogeography and functional traits predict long-term patterns of community turnover - Alistair G Auffret; Elsa Aggemyr; Jan Plue; Mora Aronsson; Lena Jonsell; Sebastian Sundberg; Sara A O Cousins (Stockholm University, 2016)
This is the dataset for the article "Spatial scale and specialization affect how biogeography and functional traits predict long-term patterns of community turnover" by Auffret et al. (2016, Functional Ecology - DOI: 10.1111/1365-2435.12716)

The data presented include the observations of plant species on 27 islands in the Stockholm archipelago in 1908 and 2008, as well as occurrences from the 2.5 x 2.5 km grid squares regional plant atlas over the same area from both 1929 and 2010. Plant functional trait values (from trait databases), plus biogeographical variables for islands and grid squares are also included.

Further details are available in the readme file, as well as the original publication.

Please feel free to get in touch.
Keywords: 60208 Terrestrial Ecology; Biological Sciences; Biologi